In Vitro Antioxidant Activity of Various Extracts of Ginger (Zingiber officinale L.) Seed - Yesiloglu, Yesim; Aydin, Hatice; Kilic, Ismail (Asian Journal of Chemistry, 2013)
The methanolic and ethanolic extracts from ginger (Zingiber officinale L.) seed (ZOS) were investigated for their antioxidant and radical scavenging activities in eight different assays, namely, total antioxidant activity, reducing power, 1,1-diphenyl-2-picryl-hydrazyl (DPPH) free radical scavenging, superoxide anion radical scavenging, hydrogen peroxide scavenging, total flavonoid content, total phenolic compound and metal chelating activities. Both methanolic extract and ethanolic extract of Zingiber officinale L. seed exhibited strong total antioxidant activity. These various antioxidant activities were compared with synthetic antioxidants such as butylated hydroxyanisole, butylated hydroxytoluene, Trolox, a-tocopherol and ascorbic acid. The methanol extract of Zingiber officinale L. seed exhibited greater antioxidant capacity than that of ethanol.